The proteomic signature of circulating extracellular vesicles following intracerebral hemorrhage: Novel insights into mechanisms underlying recovery - Laura Casado-Fernández; Fernando Laso-García; Dolores Piniella; Mari Carmen Gómez-de Frutos; Laura Otero-Ortega; Susana-Belén Bravo; Blanca Fuentes-Gimeno; Félix Docando; Elisa Alonso-López; Gerardo Ruiz-Ares; Jorge Rodríguez-Pardo; Ricardo Rigual; et al. (Neurobiology of Disease, 2024)
Circulating extracellular vesicles (EVs) can participate in innate repair processes triggered after intracerebral hemorrhage (ICH). We aimed to describe changes in the proteomic profile of circulating EVs between the acute and subacute phases of ICH and to compare the findings depending on outcomes, as an approach to unraveling such repair mechanisms.This was a prospective observational study including patients with non-traumatic supratentorial ICH. Exclusion criteria were previous disability, signs of herniation on baseline computed tomography, or limited life expectancy. EVs were isolated from blood samples at 24 h and 7 days after symptom onset. After 6-months' follow-up, patients were dichotomized into poor and good outcomes, defining good as an improvement of >10 points or > 50 % on the National Institutes of Health Stroke Scale and a modified Rankin Scale of 0–2. The protein cargo was analyzed by quantitative mass spectrometry and compared according to outcomes.Forty-four patients completed follow-up, 16 (35.5 %) having good outcomes. We identified 1321 proteins in EVs, 37 with differential abundance. In patients with good outcomes, proteins related to stress response (DERA, VNN2, TOMM34) and angiogenesis (RHG01) had increased abundance at 7 days. EVs from patients with poor outcomes showed higher levels of acute-phase reactants (CRP, SAA2) at 7 days compared with 24 h.In conclusion, the protein content of circulating EVs in patients with ICH changes over time, the changes varying depending on the clinical outcome, with greater abundance of proteins potentially involved in the repair processes of patients with good outcomes.